2020
DOI: 10.1021/acs.jafc.9b07694
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Four Optical Isomers of Antiviral Agent NK0209 and Determination of Their Configurations and Activities against a Plant Virus

Abstract: Previously, we reported for the first time that harmala alkaloids harmine and tetrahydroharmine exhibit activity against plant viruses, and we developed an analogue, designated NK0209, that efficiently prevents and controls plant virus diseases. Here, to investigate the influence of the spatial configuration of NK0209 on its antiviral activities, we synthesized its four optical isomers, determined their configurations, and evaluated their activities against tobacco mosaic virus. All four isomers were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In 2020, Song and co-workers 111 reported that all the four isomers of the antiplant virus drug NK0209 are effective in the prevention and control of the diseases caused by plant viruses. All the four isomers of the NK0209 were independently synthesized and the effects of them on antiviral activities against TMV were studied.…”
Section: Harmine-containing Natural Products Formentioning
confidence: 99%
“…In 2020, Song and co-workers 111 reported that all the four isomers of the antiplant virus drug NK0209 are effective in the prevention and control of the diseases caused by plant viruses. All the four isomers of the NK0209 were independently synthesized and the effects of them on antiviral activities against TMV were studied.…”
Section: Harmine-containing Natural Products Formentioning
confidence: 99%
“…The anti-TMV inactivating, curative, and protective activities of compound 48 were 59, 63 and 60% at 500 mg/L, respectively ( Huang et al, 2018 ). Compound 49 showed excellent inactivating, curative, and protective activities against TMV with EC 50 values of 127, 156, and 108 mg/L, respectively ( Wang and Song, 2020c ). Compound 50 not only retarded TMV proliferation, but also had a concentration-dependent effect on tobacco growth and biomass accumulation ( Zhang X. et al, 2021 ).…”
Section: Antiviral Active Compoundsmentioning
confidence: 99%
“…Additionally, (19) shown fungicidal effects against Cercospora arachidicola Hori, Alternaria solani, Bipolaris maydis, and Rhizoctonia solani [28] . On the basis of compound (11), further compounds (12) For the total prevention and control of TMV viral disease in the field, NK0209 was the first drug to be successful [27] .…”
Section: Anti-tmv Activitymentioning
confidence: 99%